Some Properties of Solutions of a Functional-Differential Equation of Second Order with Delay - Veronica Ana Ilea; Diana Otrocol (The Scientific World Journal)
Existence, uniqueness, data dependence (monotony, continuity, and differentiability with respect to parameter), and Ulam-Hyers stability results for the solutions of a system of functional-differential equations with delays are proved. The techniques used are Perov’s fixed point theorem and weakly Picard operator theory.